Der Mindestlohn in der Pflegebranche – Die Folgen eines Mindestlohns in einer Wachstumsbranche - Katrin Harsch; Hans Verbeek (Journal for Labour Market Research, 2012)
– The introduction of a minimum wage in the care sector in August 2010 was the first time that a minimum wage was introduced in a health sector. Furthermore, in contrast to other industries with minimum wages, the care sector has continually increased in recent years. Our results show that especially East German facilities were affected by the minimum wage, while most West German facilities paid significantly higher wages already prior to the introduction. Therefore, for East Germany wage effects can be found, whereas no effects on employment can be identified.
Keywords: J38; J20; I11; I18; 330; Mindestlohn - Erfolgskontrolle; Pflegeberufe; Lohnhöhe; Beschäftigungseffekte; Mindestlohnrecht; Pflegedienst; Altenheim; Altenpflege; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland